plz do fast plz i will mark you as a brilliant
Attachments:
![](https://hi-static.z-dn.net/files/dc9/283cde096f1499b9c27f489c499b6488.jpg)
Answers
Answered by
0
Answer:
Hope it helps.. sorry if it's incomplete
Attachments:
![](https://hi-static.z-dn.net/files/dc9/44ec86e050f6f9b4f06964059ca8be54.jpg)
Answered by
1
(2a + 3b) ² – 5(2a + 3b) – 14
Taking –5(2a + 3b) as a sum
=> (2a + 3b) ² + 2(2a + 3b) – 7(2a + 3b) –14
Take (2a + 3b) as common for the first 2 terms
=> (2a + 3b) (2a + 3b + 2) – 7(2a + 3b) –14
Take –7 common
=> (2a + 3b) (2a + 3b + 2) – 7(2a + 3b + 2)
Taking (2a + 3b + 2) common
=> (2a + 3b + 2) (2a + 3b –7)
>> (2a + 3b +2) (2a + 3b – 7) is the answer
Similar questions